Pengaruh Beban Kerja Terhadap Kinerja Karyawan melalui Work Life Balance (Studi Kasus PT. Telkom Indonesia Regional V) - NURWAHYUNI, SITI (Jurnal Ilmu Manajemen (JIM), 2018)
The aim of this study to know and analyze the effect of workload on employee performance with mediated by work life balance. The data was obtained by the results of questionnaires and interviews. The sample used in this study were 73 employees taken with saturated sampling method. This study uses a quantitative approach obtained by observation, interview and spread the questionnaire. Data analysis technique Partial Least Square (PLS) is the analysis that used in research. The results show that the workload was not gave asignificant impact toemployeeperformance of PT. Telkom Indonesia Regional V, however further analysis is related to workload and employee performance by using married employees showed that workload has not significant impact to employee performance. Workload has a significant negative impact on work life balance. Work life balance has a significant positive impact on employee performance. Work life balance mediate workload on employee performance. Keywords: workload, employee performance, work life balance